Performance Management Systems in Czech Companies: Findings from a Questionnaire Survey - Stříteská, Michaela; Zapletal, David; Jelínková, Lucie (My University, 2016)
Measuring and managing performance is an integral part of contemporary management systems, which are focused on achieving outstanding business results. This is based on a systematic, comprehensive review of a company's activities and results with the goal of identifying weaknesses and opportunities for improvement. Therefore, it is put more emphasis on the development of an effective performance measurement and management system as a tool for enhancing business competitiveness. Given the importance and urgency of this issue the revolutionary developments in this area can be observed over the last 20 years. Researchers and managers are constantly trying to understand all the variables affecting the performance of the company. They are looking for an answer to the question of how best to use the lessons learned from performance measurement to its management. They design and develop various concepts, frameworks and methods for measuring and managing performance in the current business practice. They are constantly trying to eliminate the drawbacks of contemporary systems in order to increase their effectiveness. Cognition of these systems, their characteristics and identification of weaknesses can be seen as challenges for performance measurement and management in the future, for which solutions must be found. Therefore, the primary goal of this paper is to investigate the level of development of current performance management systems in Czech companies. The level of development is determined by fulfilment of the characteristics of an effective performance management system based on literature review. Attention is also paid to determination whether the level of a performance management system's development is dependent on company size. The method of an electronic questionnaire was selected for acquiring data.
Systémy řízení výkonnosti v českých podnicích: závěry z dotazníkového šetření
Keywords: Performance; measurement; management; system; Výkonnost; měření; management; systém